Analysis of Psychological Factors in the Process of Memorizing the Quran - Azalia, Elgita Azka; Jenuri, Jenuri (Bestari, 2025)
Memorizing the Quran, an act revered across the Islamic world, stands as a profoundly virtuous form of worship. Beyond its spiritual significance, this endeavor demands considerable cognitive and psychological engagement. The primary objective of our research was to meticulously analyze the essential psychological factors that play a crucial role in this complex process of Quran memorization. To achieve this, we employed a literature review approach, systematically gathering and analyzing a wide array of relevant scholarly literature pertaining to psychological factors in Quran memorization. This method allowed us to build a comprehensive understanding from various existing perspectives. Our analysis revealed that several key psychological factors indeed significantly impact the Quran memorization process. Specifically, we found that motivation, both intrinsic (arising from within, like love for Allah) and extrinsic (triggered by external factors, like social support), serves as a primary driver for individuals to engage in memorization efforts. High concentration and sustained focus are also paramount in ensuring the effectiveness and speed of the learning process. Furthermore, a strong interest in the Quran can considerably enhance motivation and perseverance in memorizing its verses. Not to be overlooked, self-efficacy, or one's belief in their ability to perform an action and overcome obstacles, also plays a vital role in determining success. Conversely, anxiety emerged as a potential hindrance that can disrupt concentration and impede the memorization process.